(Mis)use of Prescribed Stimulants in the Medical Student Community: Motives and Behaviors. Issue 16 (April 2016) - Fond, Guillaume; Gavaret, Martine; Vidal, Christophe; Brunel, Lore; Riveline, Jean-Pierre; Micoulaud-Franchi, Jean-Arthur; Domenech, Philippe
Abstract : Abstract: The aim of this study was to estimate the prevalence of psychostimulant use in the French medical community and their motives. A population-based cross-sectional study using a self-administered online survey was done. A total of 1718 French students and physicians (mean age, 26.84±7.19 years, 37.1% men) were included. Self-reported lifetime use, motives, socio-demographic and academic features for over the counter (OTC), medically prescribed (MPP), and illicit (IP) psychostimulant users were reported. Lifetime prevalence of psychostimulant use was 33% (29.7% for OTC, 6.7% for MPP, and 5.2% for IP). OTC consumption mainly aimed at increasing academic performance and wakefulness during competitive exams preparation. OTC consumption started early and was predictive of later MPP use. Corticoids were the most frequently consumed MPP (4.5%) before methylphenidate and modafinil. Motives for MPP consumption were increased academic performance, concentration, memory, and wakefulness. Psychostimulant use is common among French medical community. Our results suggest that restrictions on methylphenidate and modafinil prescriptions are effective at limiting their use. However, these restrictions may explain the observed rates of corticoids consumption, which raise a new public health problem, given that corticoids may have severe side effects.